2019
DOI: 10.3389/fcimb.2019.00134
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma Hypervirulence in the Rat Model Parallels Human Infection and Is Modulated by the Toxo1 Locus

Abstract: Toxoplasmosis is considered as an opportunistic parasitic disease. If post-natally acquired in children or adults, it may pass unnoticed, at least with strains of European origin. However, in the wild biotopes especially in South America, Toxoplasma gondii strains display a greater genetic diversity, which correlates to higher virulence for humans, particularly along the Amazon River and its tributaries. In French Guiana, several atypical strains have been associated with severe clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
(51 reference statements)
2
12
0
Order By: Relevance
“…Real-time PCR was used to monitor the distribution of T. gondii in different murine tissues during the infection with 10 2 or 10 6 tachyzoites (IP) of the RH strain, or 10 cysts (PO) of the ME49 strain ( Djurković-Djaković et al., 2012 ); this study concluded that the level of parasite burden in the lungs seemed to be critical for mice survival/parasite virulence. This result agrees perfectly with what was observed previously ( Loeuillet et al., 2019 ), where pneumomegaly, and the greater parasitic load and tissue destruction in the lungs were strongly associated with the hypervirulence of the non-canonical GUY008-ABE isolate (haplogroup 5, ToxoDB # unknown). On the other hand, some studies pointed out ocular tropism as a virulence related trait, with a more frequent parasite DNA detection in ocular tissues from mice infected with more virulent strains ( Hamilton et al., 2019 ; Chiebao et al., 2021 ; Fernández-Escobar et al., 2021 ).…”
Section: Complementary Approaches On the Determination Of Virulence I...supporting
confidence: 93%
See 3 more Smart Citations
“…Real-time PCR was used to monitor the distribution of T. gondii in different murine tissues during the infection with 10 2 or 10 6 tachyzoites (IP) of the RH strain, or 10 cysts (PO) of the ME49 strain ( Djurković-Djaković et al., 2012 ); this study concluded that the level of parasite burden in the lungs seemed to be critical for mice survival/parasite virulence. This result agrees perfectly with what was observed previously ( Loeuillet et al., 2019 ), where pneumomegaly, and the greater parasitic load and tissue destruction in the lungs were strongly associated with the hypervirulence of the non-canonical GUY008-ABE isolate (haplogroup 5, ToxoDB # unknown). On the other hand, some studies pointed out ocular tropism as a virulence related trait, with a more frequent parasite DNA detection in ocular tissues from mice infected with more virulent strains ( Hamilton et al., 2019 ; Chiebao et al., 2021 ; Fernández-Escobar et al., 2021 ).…”
Section: Complementary Approaches On the Determination Of Virulence I...supporting
confidence: 93%
“…Complementarily, parasite proliferation was evaluated in vitro in primary rat peritoneal macrophages. Final findings in this model demonstrated the hypervirulent phenotype of the South American (French Guiana) GUY008-ABE strain in contrast to the avirulent profile of PRU laboratory strain ( Loeuillet et al., 2019 ). Recently, guinea pigs were also proposed as a suitable model for human congenital toxoplasmosis in experimental infections of pregnant guinea pigs being administered 10, 100 or 500 oocysts of T. gondii strain ME49 at different time points during gestation ( Grochow et al., 2021 ).…”
Section: In Vivo Models For Virulence Assessment: State and ...mentioning
confidence: 81%
See 2 more Smart Citations
“…This locus contains a nucleotide-binding oligomerization domain, leucine-rich repeat protein 1 ( NLRP1 ), which encodes for the NLRP1 inflammasome sensor that causes rapid cell death and disruption of the replicative niche of the parasite upon activation (Cirelli et al, 2014 ). One exception is the South American strain GUY008-ABE, which can establish a chronic infection in Lewis rats and is fatal to F334 rats (Loeuillet et al, 2019 ). Thus, although it is in the parasite's best interest to cause a lifelong chronic infection, it is clear that not every parasite strain can produce an optimal infection in every animal.…”
Section: Introductionmentioning
confidence: 99%